2009
DOI: 10.1159/000265117
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Plasma Antidiuretic Hormone, Electrocochleography, and Glycerol Test in Patients with Endolymphatic Hydrops

Abstract: Objective: To investigate the relationship between the plasma antidiuretic hormone (p-ADH) level, electrocochleogram (ECoG), and the glycerol test in patients with endolymphatic hydrops (ELH). Patients and Methods: The subjects were 60 patients, including 51 with Ménière’s disease (except for cochlear Ménière’s disease), 7 with delayed ELH, and 2 with syphilitic ELH. The time period for measurements of the p-ADH level, ECoG and the glycerol test was within 4 weeks. Results: 13 patients showed positive results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In ECoG diagnosis of MD, these characteristics of ECoG must be considered. We improved the detection rate of endolymphatic hydrops by the combination of ECoG, the glycerol test and the measurement of plasma vasopressin levels [29] . If the diagnosis could be anchored in the patient's clinical history, symptoms, audiogram and dehydration tests including the glycerol test, extratympanic ECoG may play an important diagnostic role, especially in MD patients with less definite symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In ECoG diagnosis of MD, these characteristics of ECoG must be considered. We improved the detection rate of endolymphatic hydrops by the combination of ECoG, the glycerol test and the measurement of plasma vasopressin levels [29] . If the diagnosis could be anchored in the patient's clinical history, symptoms, audiogram and dehydration tests including the glycerol test, extratympanic ECoG may play an important diagnostic role, especially in MD patients with less definite symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Even taken together, the two functional tests were not competitive (only 15 patients showed a positive result in at least one test). This does not surprise considering that claims about the superiority of a combination of electrocochleography and glycerol test compared to the single tests [ 57 , 58 ] are not well founded (false positives are left unconsidered).…”
Section: Discussionmentioning
confidence: 99%
“…Kimura et al reported that 97% of 118 patients with definite MD showed at least one positive test result in a battery of three tests, and that the combination of three rather than two tests resulted in an improved diagnostic accuracy [6]. Taguchi et al also showed that 97% of 60 patients with ELH had at least one positive result in a battery of p-ADH, ECoG, and the glycerol test [8]. The furosemide test and p-ADH are highly sensitive.…”
Section: Discussionmentioning
confidence: 99%